Assessing the diagnostic accuracy of radiological and histological findings in the diagnosis of non-alcoholic fatty liver disease stages among patients in a tertiary hospital - Ekpe Edemekong L; Emanghe U; Ekpe EL; Obiora IC; Yemiode Itam; Akinmola OO (Journal of Krishna Institute of Medical Sciences University)
Background: Early screening, detection, and early intervention are life-saving modalities to lessen the impact and burden of non-communicable diseases. Aim and Objectives: To evaluate the diagnostic strength of ultrasound in the diagnosis of Non-alcoholic Fatty Liver Disease (NAFLD) stages. Material and Methods: Participants were recruited from patients with fatty liver who underwent liver biopsy and baseline ultrasound at the University of Calabar Teaching Hospital between January 2023 and December 2023. Ultrasonographic findings were correlated with the histological findings of liver biopsy which was considered the gold standard for the diagnosis of NAFLD. Results: One hundred and nine participants were recruited and participated in this study, of which 62 (56.9%) were females and 47(43.1%) were males, with the highest age bracket presenting at 56-65 years. The female-to-male ratio was 1:1.4 and their mean age was 55.5 ± 12.8 years (age range was 18-70 years). The ultrasonographic findings were correlated with histological data (considered as the gold standard). The sensitivity, specificity, Positive Predictive Value (PPV), and Negative Predictive Value (NPV) were evaluated. The ultrasonography had a sensitivity of 90.4% (95% Confidence Interval (CI): 83.6-93.6) and a specificity of 72.5% (95% CI: 68.7-79.8). The PPV and NPV were 74.7% and 65.6% respectively. The area under the curve was 84.5%. The positive likelihood ratio was 1.5 (95 CI: 1.21-1.90), and the negative likelihood ratio was 0.30 (0.17-0.54). Conclusion: Ultrasound findings were highly significant and useful in detecting advanced or late-stage steatosis in patients with fatty liver. In the future, as technology advances, it is hoped that the need for liver biopsy may not be necessary as hi-tech radiological involvement may help patients with fatty liver without the involvement of any invasive procedure.